Determining Efficacy of Tranexamic Acid in Reducing Post Partum Haemorrhage in Elective Cesarean Section Patients Evaluating in Referance to Fall in Haemoglobin - Javaria Gulzar, Sadaf Zahra, Iqra Aftab, Nayab Amir, Rana Muhammad Naeem Liaqat, Ayesha Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Obstetrical haemorrhage is a potentially fatal clinical manifestation of either vaginal delivery or caesarean section. According to reports, it is responsible for almost fifty percent of all pregnancy - related deaths. The prevalence of caesarean section (CS) has dramatically upped in both low income as well as in developed nations, thereby increasing the likelihood of obstetrical haemorrhage. The rationale of this study is that it is important to evaluate the efficacy and safety of TA on blood loss with LSCS. Methods: Cases were separated into two subgroups: case: (A) and control: (B). In the operating theater, participants were given A and B packages to choose from, the contents of whom were only known to the nurse in charge of drug preparation. All meds were injected by an anesthetist who was not in charge of supervising or assessing the patients. Results: Comparison of both %age reduction in Hb levels (>10%) after treatment shows that in Group A 6(20%) and in Group B 15(50%) had >10% reduction in Hb levels after treatment, p-value=0.015. Conclusion: TA administration reduced dramatically the bleeding throughout CS, the proportion of patients who lost more than 1000 mL of blood, and the requirement for supplemental uterotonic substances. As a result, TA can be employed very safely and successfully in patients receiving caesarean section.